Caulerpa racemosa extract inhibits HeLa cancer cells migration by altering expression of epithelial-mesenchymal transition proteins - Permatasari, Happy Kurnia; Barbara Ulfa, Ektina Naura; Adyana Daud, Vanessa Pradna; Sulistomo, Hikmawan Wahyu; Nurkolis, Fahrul (Frontiers in Chemistry, 2022)
Introduction: Cervical cancer is caused by persistent infections of human papillomavirus types 16 and 18. Also, it is classified as a malignancy since it is able to spread itself to other sites and form a metastasis. Lymph nodes metastasis is an important factor related to cervical cancer survival. The previous study reported that Caulerpa racemosa has an anti-cancer effect by inducing apoptosis by inhibiting p53 protein degradation in HeLa cancer cells. In this study, we conducted a follow-up test to determine the anticancer effect of Caulerpa racemosa as an antimetastatic agent on HeLa cancer cells. Methods: A true experimental study with a post-test-controlled group design was carried out on four groups of HeLa cell cultures by presenting different concentrations of Caulerpa racemosa extract. Moreover, to identify the antimetastatic effect, HeLa cells treated with Caulerpa racemosa extract were subjected to the woud healing scratch test and immunofluorescence staining assays. Data analysis was gained with qualitative and quantitative approaches. Quantitative methods such as One-way analysis of variance, Tukey's multiple comparison test, and Pearson's correlation were conducted. Result: We found that Caulerpa racemosa significantly inhibit HeLa cells wound healing migration. We also demonstrated the effect of Caulerpa racemosa in downregulating Snail and Vimentin protein expression and upregulating E-Cadherin protein expression. Conclusion: Caulerpa racemosa extract inhibits HeLa cancer cells migration by altering important regulator proteins expressions of epithelial-mesenchymal transition pathways.